Influência da força e potência muscular sobre o desempenho físico de indivíduos com DPOC - Bueno, Leonardo Garbin (Universidade Federal de São Carlos, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is considered a major cause of morbidity and mortality worldwide. In addition to pulmonary changes, several extrapulmonary manifestations can appear with the worsening of the disease, among the most prevalent is muscle dysfunction, which consequently generates less physical performance. Despite the previous literature addressing the relationship between these two aspects, there are still gaps on the influence of the components of muscle function on physical performance, assessed by different functional tests. Aim: To analyze the influence of quadriceps muscle function on physical performance, assessed using the 6-minute walk test (6MWT) and the 6-minute step test (6MST), in individuals with chronic obstructive pulmonary disease (COPD). Methods: This is a cross-sectional and observational study that evaluated individuals with COPD of both sexes, aged between 60 and 80 years. It took two days of evaluations with an interval of one week, in which evaluations were carried out as anamnesis; body composition with electrical bioimpedance equipment; dyspnea and daily physical activity with the mMRC scale and the DASI questionnaire, respectively; quadriceps muscle function by a computerized dynamometer and physical performance by Six Minute Step Test (6MST) and Six Minute Walk Test (6MWT). The sample size calculation was performed using G* Power software version 3.1.9.2. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) version 21.0. Data distribution was verified by the Shapiro-Wilk normality test. Variables with parametric distribution were expressed as mean ± standard deviation, while variables with non-parametric distribution were expressed as median and interquartile range. To analyze the correlations, Pearson's correlation coefficients were used for parametric variables and Spearman's for non-parametric variables. Then, if there was a correlation between the variables (strength, endurance or power with 6MWT and 6MST), a multiple linear regression model would be applied to verify the influencing factors (strength, endurance and power) in the main outcome variable (physical performance – 6MWT and 6MST – separately). Results: The peak torque - 60°/s (Nm) and power - 90°/s (W) had a strong positive correlation with the 6MST (r = 0.729 and 0.725 respectively; p ≤ 0,000). Muscle powers - 60°/s and 90°/s (W) showed a moderate positive correlation with the 6MWT (r = 0.576 and 0.596 respectively; p ≤ 0,010). The results of multiple linear regressions showed that the peak torque - 60°/s (Nm) was the variable with significant participation in the model with the 6MST (adjusted R² = 0.504; p ≤ 0,000). For the model involving the 6MWT, the only variable included was muscle power - 90°/s (W) (adjusted R² = 0.318; p ≤ 0,007). Conclusion: The quadriceps muscle function differently influences the physical performance assessed by means of the 6MST and 6MWT. While muscle strength was able to explain performance in the 6MST more, muscle power had more influence on the 6MWT variation. These findings showed that the strength and power of the quadriceps muscle can significantly influence the performance of physical activities such as walking up and down steps and walking.
Influence of muscle strength and power on physical performance of individuals with COPD
Keywords: Fisioterapia; Doença Pulmonar Obstrutiva Crônica; Dinamômetro de força muscular; Desempenho físico; Exercício; Physiotherapy; Pulmonar Disease Chronic Obstructive; Muscle strength dynamometer; Physical performance; Exercise; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL